TAHAPAN PROSES BERPIKIR KREATIF SISWA MELALUI REALISTIC MATHEMATICS EDUCATION - Vivi Novitasari; Mohammad Faizal Amir (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2021)
One approach to learning based on contextual problems, namely Realistic Mathematics Education (RME), has been proven to explore and improve students' creative thinking. This study aims to identify RME steps to improve students' creative thinking that refers to the principles and characteristics of RME. This research uses a literature study. There are five stages of students' creative thinking process through RME: the orientation stage of students reading and understanding problems. Students reread the problem, look for information from books, and ask the teacher in the preparation stage. In the incubation stage, students reread the information obtained from the preparation stage and formulate strategies. Students think about ideas, analyze ideas, connect and link ideas into solutions, and solve problems in the illumination stage. Verification stage, students check ideas or answers.